How Corporate Social Responsibility Culture Sparks Innovation: Evidence From Malaysian Employees - Louis Yong Yu Lee; Jamin Kun Peng Xia; Ranjith P V; Huey Min Beh; Baiduri Binti Khalid; Tiantian Cai; Yangpeng Cai; Lakshmi L; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2025)
This study examines how the organizational corporate social responsibility climate (OCSRC) influences employees’ innovative job performance through the mediating roles of job satisfaction, work motivation, and employee creativity. Using a quantitative design, data were collected from 153 full-time employees in Malaysia. Regression analyses revealed that OCSRC significantly enhances job satisfaction (? = 0.896, p 0.001), work motivation (? = 0.276, p 0.001), and employee creativity (? = 0.213, p 0.01). Job satisfaction positively affects work motivation (? = 0.607, p 0.001) and creativity (? = 0.217, p 0.01), while work motivation influences both creativity (? = 0.429, p 0.001) and innovative job performance (? = 0.176, p 0.05). Employee creativity emerges as the strongest determinant of innovation (? = 0.880, p 0.001). The model explains 83.5% of the variance in innovative job performance (R² = 0.835). These results confirm that CSR climate indirectly drives innovation through satisfaction, motivation, and creativity, aligning with Social Exchange and Self-Determination theories. The study contributes by positioning CSR as an internal strategic resource that enhances psychological engagement and innovation in Malaysian organizations